2010
DOI: 10.1021/om100480v
|View full text |Cite
|
Sign up to set email alerts
|

Triphenylphosphane-Modified Cobalt Catalysts for the Selective Carbonylation of Ethyl Diazoacetate

Abstract: The triphenylphosphane-substituted carbonyl cobalt complexes Co2(CO)7(PPh3), Co2(CO)6(CHCO2Et)(PPh3), and [Co(CO)3(PPh3)2][Co(CO)4] were found to be more effective precatalysts in the carbonylation of ethyl diazoacetate under atmospheric pressure of carbon monoxide at 10 °C in dichloromethane solution than the parent Co2(CO)8 and Co2(CO)7(CHCO2Et) complexes. The highly reactive (ethoxycarbonyl)ketene is the primary product of the catalytic carbonylation, which dimerizes in the absence of a proper scavenger. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
0
13
1
Order By: Relevance
“…DFT calculations have suggested that the Pd-catalyst is not only involved in the ketene formation process but also plays a role in the [2 + 2] cycloaddition process which may affect the diastereoselectivity of the products (Scheme e). Compared with the Co 2 (CO) 8 -catalyzed or -mediated carbonylation of EDA with CO involving the formation of ketene intermediate, the Pd-catalyzed protocol provides a general route to ketene compounds and is expected to be widely used in organic synthesis owing to the broad substrate scope of carbene precursors and the mild reaction conditions (with atmospheric pressure of CO). Later, similar transformations were also achieved under the catalysis of other transition-metal complexes. …”
Section: Pd-catalyzed Carbene Coupling Reactionsmentioning
confidence: 98%
“…DFT calculations have suggested that the Pd-catalyst is not only involved in the ketene formation process but also plays a role in the [2 + 2] cycloaddition process which may affect the diastereoselectivity of the products (Scheme e). Compared with the Co 2 (CO) 8 -catalyzed or -mediated carbonylation of EDA with CO involving the formation of ketene intermediate, the Pd-catalyzed protocol provides a general route to ketene compounds and is expected to be widely used in organic synthesis owing to the broad substrate scope of carbene precursors and the mild reaction conditions (with atmospheric pressure of CO). Later, similar transformations were also achieved under the catalysis of other transition-metal complexes. …”
Section: Pd-catalyzed Carbene Coupling Reactionsmentioning
confidence: 98%
“…The process is more exergonic for the cobalt complex in comparison to that for the ethoxycarbonyl carbene analogue (−18.3 kcal/mol as opposed to −7.0 kcal/mol) and takes place with a much smaller barrier (1.6 kcal/mol as opposed to 15.5 kcal/mol) [8]. For the rhodium pathway Δ = −13.3 kcal/mol has been obtained as reaction free energy with a small barrier of 5.4 kcal/mol.…”
Section: Resultsmentioning
confidence: 91%
“…The main goal of this study is to further explore computationally the reactivity of simple carbonyl carbene radicals, which have already proven their applicability in the carbonylation of ethyl diazoacetate [8]. The second purpose is to scrutinize the vertical trends in the cobalt group of transition metals and to investigate the reaction profile for the rhodium and iridium analogues and to check whether the equilibrium can be on the carbene side in some cases, like it was reported by Urtel and coworkers [7].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Triphenylphosphine-substituted cobalt carbonyl complexes were found to be even more active precatalysts in the carbonylation of EDA. With two equivalents of PPh 3 , the presence of the ion pair [Co(CO) 3 (PPh 3 ) 2 ][Co(CO) 4 ] could be observed, which was assumed to interconvert to the corresponding radical pair under catalytic conditions [ 21 ].…”
Section: Introductionmentioning
confidence: 99%